Constructing a national identity in media editorials to promote affiliation with an international readership. (October 2021) - Liu, Feifei; Chang, Chenguang
Abstract: Media discourse is acknowledged as a significant site for propagating a construal of national identity. To date, research interest has focused largely on how the media supports a relatively stable concept of national identity, around which bonds with people internal to the nation are tendered and reinforced. In this study, the focus shifts to the role of the media in promoting a national identity externally to an international readership. The data comprise 10 editorials from China Daily, an influential English-language state newspaper of China with a global circulation. Analyses draw on Systemic Functional Linguistic (SFL) theory, specifically the discourse-semantic systems of attitude and ideation . The study explores how couplings of evaluation (expressions of attitude ) and entities (expressions of ideation ) are expressed and how they contribute to rhetorical strategies through which national identity is construed and tendered to an international readership in the interest of promoting affiliation. Analyses of ideation point to two key roles played by the entity China with respect to the figure of building international relations : that of an agent which instigates a figure (as in China supports X to do Y) and that of a source which takes a position on a figure (as in China proposes that X does Y). These structures configure China as a promoter of positive international relations. The analysis offers a functional linguistic contribution to research on identity construction, affiliation and the persuasive power of media discourse.